Refractive Surgery: Part 2. Complications and recent advances - Eltis, Mark (Canadian Journal of Optometry, 2022)
While LASIK and PRK have been used for two decades, there have been few long-term studies on refractive surgery. This study examined the long-term outcomes of LASIK and PRK and analyzed the risks, benefits, and technological breakthroughs of these procedures. Rates and causes of patient satisfaction are discussed in detail. Alternative techniques such as small-incision lenticule extraction (SMILE) and surgical options for presbyopia are also explored.